Regional policies for innovation: the case of technology districts in Italy. Issue 12 (2nd December 2017) - Bertamino, Federica; Bronzini, Raffaello; De Maggio, Marco; Revelli, Davide
ABSTRACT: Regional policies for innovation: the case of technology districts in Italy. Regional Studies . This paper studies a policy tool implemented in Italy in the last decade to foster local innovation activity called technology districts. First, it examines the characteristics of technology districts and those of the firms within them. Next, it assesses the performance of district firms. The South of Italy has more technology districts, but they are small, poorly sectorially diversified and far from the economic structure of the area. Firms that did join a district had previously been, on average, larger, more innovative and profitable, and show also higher leverage than the others. After the institution of a district the performance of the firms that joined it did not differ significantly from that of similar firms that did not.